Chronic Δ9-tetrahydrocannabinol impact on plasticity, and differential activation requirement for CB1-dependent long-term depression in ventral tegmental area GABA neurons in adult versus young mice - Ostlund, Isaac; Von Gunten, Michael; Smith, Calvin; Edwards, Jeffrey G. (Frontiers in Neuroscience, 2023)
The ventral tegmental area (VTA) mediates incentive salience and reward prediction error through dopamine (DA) neurons that are regulated by local VTA GABA neurons. In young mice, VTA GABA cells exhibit a form of synaptic plasticity known as long-term depression (LTD) that is dependent on cannabinoid 1 (CB1) receptors preceded by metabotropic glutamate receptor 5 (mGluR5) signaling to induce endocannabinoid production. This LTD was eliminated following chronic (7–10 consecutive days) exposure to the marijuana derived cannabinoid Δ9 -tetrahydrocannabinol (THC). We now examine the mechanism behind THC-induced elimination of LTD in adolescents as well as plasticity induction ability in adult versus young male and female mice using whole-cell electrophysiology experiments of VTA GABA cells. Chronic THC injections in adolescents resulted in a loss of CB1 agonist-mediated depression, illustrating chronic THC likely desensitizes or removes synaptic CB1. We noted that seven days withdrawal from chronic THC restored LTD and CB1 agonist-induced depression, suggesting reversibility of THC-induced changes. Adult mice continue to express functional mGluR5 and CB1, but require a doubling of the synaptic stimulation compared to young mice to induce LTD, suggesting a quantitative difference in CB1-dependent plasticity between young and adult mice. One potential rationale for this difference is changes in AMPA and NMDA glutamate receptors. Indeed, AMPA/NMDA ratios were increased in in adults compared to young mice. Lastly, we performed quantitative reverse-transcription PCR and identified that CB1, DAGLα, and GluA1 levels increased following chronic THC exposure. Collectively, our data demonstrate the first age-dependent GABA neuron plasticity in the VTA, which could have implications for decreased THC dependence capacity in adults, as well as the mechanism behind chronic THC-induced synaptic alterations in young mice.